ANALYSIS OF BUSINESS FAILURE OF NNS BATAM EDUTAINMENT PARK FROM AN EDUPRENEURSHIP PERSPECTIVE - Lubis, Arina Luthfini; Supardi, Supardi; Wibowo, Andri; Fatimah, Zahara (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The failure of edutainment ventures has become an important issue in the field of educational entrepreneurship (edupreneurship), particularly in Indonesia where empirical studies on local edutainment practices remain limited. This study aims to analyze the factors contributing to the failure of NNS Batam, a role-play-based edutainment park for children that operated from 2019 to 2024, using a qualitative case study approach. Data were collected from four categories of informants—former managers, former employees, visitors, and edupreneurship scholars—through semi-structured interviews, location observation, and digital documentation. Thematic analysis revealed that the failure was not solely caused by external disruptions such as the COVID-19 pandemic but also by internal weaknesses including poor business strategy, lack of meaningful integration of educational values, absence of continuous innovation, and inadequate evaluation mechanisms. A notable gap was found between the company’s educational vision and its operational practices. Expert informants emphasized that sustainable edupreneurship requires synergy between pedagogical value and financial strategy. This study contributes to a deeper understanding of edutainment business failures in emerging urban contexts and offers practical insights for edupreneurs seeking to design adaptive, value-driven, and resilient education-based ventures.